Sales and Employment Changes in Entrepreneurial Ventures with Family Ownership: Empirical Evidence from High‐Tech Industries. (April 2014) - Colombo, Massimo G.; De Massis, Alfredo; Piva, Evila; Rossi‐Lamastra, Cristina; Wright, Mike; Carsrud, Alan; Cucculelli, Marco
<x xml:space="preserve">Abstract</x> We examine the relation between changes in employment and changes in sales for entrepreneurial ventures with and without family ownership. We argue that this positive relation is weaker for entrepreneurial ventures with family ownership. The goal of preserving socio‐emotional wealth (SEW) makes indeed these firms more reluctant to hire (fire) employees in correspondence with an increase (decrease) in sales than their counterparts without family ownership. Results on a sample of Italian entrepreneurial ventures in high‐tech industries support our arguments. They also show that the strength of the relation depends on the composition of the entrepreneurial team.